Responses to salinity in the littoral earthworm genus Pontodrilus - Teerapong Seesamut; Beewah Ng; Chirasak Sutcharit; Ratmanee Chanabun; Somsak Panha (Scientific Reports, 2022)
Abstract The cosmopolitan littoral earthworm Pontodrilus litoralis is distributed in tropical and sub-tropical coastal habitats, whereas P. longissimus is reported only in the Thai-Malay coastal line. In the present study, we examined the difference in salinity effect on the survival rate, wet weight (hereafter weight) change, behaviour, and osmolality of these two Pontodrilus species. A 28 d exposure to varying salinity concentration (0–50 ppt) revealed that P. litoralis is able to survive over a wide salinity range than P. longissimus, with the latter species exhibiting a low survival rate over the same salinity range. During short-term exposure (0–96 h) to a salinity of less than 30 ppt, P. litoralis exhibited weight gain and this was significant in the first 12 h of exposure. However, P. longissimus gained weight when exposed to salinity at under 10 ppt in the first 72 h of exposure. The two species of Pontodrilus behaved differently when exposed to different salinities. The coelomic fluid osmolarity of Pontodrilus was related to the exposure medium and was mostly maintained as hyperosmotic to the external medium over the range of salinities tested. This study shows how two different species of the littoral earthworm genus Pontodrilus respond to a change in salinity, which may explain their dispersal pattern and shape their distribution pattern throughout Southeast Asia.